TEOLOGIA E TRADIÇÃO NO CONTEXTO DAS RELIGIÕES DE UMBANDA: UMA ANÁLISE DO CONFLITO ENTRE CULTURA ACADÊMICA E POPULAR - RODRIGUES, Júlio César Pasqualinoto (2016)
Umbanda religion occupies a large space in life and in the Brazilian religious imagery, and adopts the legends, myths and folklore of Brazilian popular culture. Devoid of sacred text, Umbanda rejects the idea of understanding of a sacred literature as a prerequisite for a connection with the divine, being more concerned with religious and sacred experience as a bridge between the human and divine dimension. Although in agreement on the importance of practice in the Umbanda religion, there is a strong theological debate on the question of the principal amount to the practices and religious life of the saint's son. On the one hand, we have the esoteric doctrine that focus on textual and theoretical production and on the other, we have the popular Umbanda, which focuses on personal experience saint's son with the oral tradition and religious practices. From its founding to the present, Umbanda Esoteric has focused on academic education as the main basis for the saint’s child of instrumentalization for practice in the yard, as well as publication of texts, books, articles, offering courses and the creation of the first specialized institution of education, the Theological Faculty Umbanda. On the one hand, for some, this may seem an opening for the modernization and better acceptance of African origin practices for others, is a limitation in practice and saint son of experience due to the rationality of academic space. Thus, I intend to investigate this conflict in speech and in their specificities, studying specialized and organic literature, and as research axis the following question: What is more important to the religious practices of Umbanda, practical training or academic?